ISSUES OF TURKESTAN HISTORY IN THE WORKS OF SADRIDDIN AINI (Scientific journal of the Fergana State University, 2023)
This article scientifically analyzes the scientific and creative activity of Sadriddin Aini, historian, famous writer and public figure, and studies the issues of socio-economic and cultural life of Turkestan in the late XIX and early XX century, the situation of the local population, achievements and problems in the scientific activity of the region, and also highlights the importance and essence of the works of this author "History of the Bukhara emirs", "Materials for the history of Bukhara Revolution", "Memories" and articles devoted to relevant problems of Turkestan history.